Perancangan Sistem Manajemen Mutu ISO 9001:2015 pada PT Cakratek Buana Amerta - Evander Eric; Jani Rahardjo (Jurnal Titra, 2020)
PT Cakratek Buana Amerta is a company engaged in the field of chemical construction. Business competition that has become increasingly fierce makes PT Cakratek Buana Amerta strive to have an ISO 9001:2015 certificate to prove that the company has determined its commitment to always focus on customer satisfaction. This study aims to assist companies in designing the ISO 9001:2015 quality management system in the company. The research methodology used in this study is to look at the condition of the company in real terms and conduct an initial gap analysis to find out the documents that are owned by the company and which are not yet owned by the company. Documents that are not yet owned by the company will be assisted to be made while documents that are not in accordance with ISO 9001:2015 standards will be assisted to be improved. After the preparation and improvement of documents has been completed a final gap analysis will be conducted to determine the percentage increase in document fulfillment for the company. The results of the final gap analysis showed a percentage increase in document fulfillment for the company by 43.01%, where in the initial gap analysis the percentage of document fulfillment reached 34.06% and increased in the final gap analysis reaching 77.07%.